Start-ups' accelerators support open innovation in Portugal. (7th May 2019) - Fernandes, Silvia; Castela, Guilherme
Modern competitiveness is tough, mainly due to new technologies and platforms. Managers must cope with these challenges to keep their businesses innovative and successful. An important step is to exploit the potential of open innovation. This work analyses where Portugal stands in terms of innovation in general, propensity for open innovation and innovation sustainability. A HJ-Biplot methodology was applied to a valid sample from the community innovation survey (CIS) for Portugal. The analysis suggests that Portuguese firms must cut back on activities that are not leading to the right outcomes. And the choice of right partners can cause more ideas to be executed and diffused. Innovation accelerators can help in this approach toward better innovation turnovers and country's innovation index. These issues are relevant to research in the face of fast trends such as the fourth industry (IoT, cyber-physical environments) and smart cities.